Transformasi Pendidikan Melalui Penggunaan Chatbot: Manfaat, Tantangan, dan Rekomendasi untuk Masa Depan - Ahmad Eko Suryanto; Marko Ayaki Lumbantobing; Ratna Pancawati (Journal on Education, 2024)
Recent research highlights the increasingly important role of chatbots in educational transformation. Through literature reviews and empirical studies, researchers have revealed that the use of chatbots in the educational context provides significant benefits for both teachers and students. From the perspective of educators, chatbots can enhance learning efficiency, facilitate interactions with students, and boost creativity in the teaching process. Meanwhile, students also experience increased accessibility to learning materials, efficiency in completing tasks, and improved interaction with learning materials. However, challenges such as the required preparation and training, as well as the need for verification of information provided by chatbots, remain a primary concern. Recommendations include enhancing preparation and training, developing more advanced chatbot technology, improving information verification, and fostering collaboration between research and educational practitioners to address challenges and maximize the potential of chatbots in future education.